A DEVICE FOR COLLECTING AND STORING BLOOD FROM A SUBJECT - DREXEL, Masao; JUNEAU, Kara; JACKSON, Alicia; BEYERLEIN, Dagmar; JORDAN, Brett L (2025)
Disclosed herein are devices, apparatus, systems, methods and kits for collecting and storing a fluid sample from a subject. A device for collecting the fluid sample can include a housing comprising a recess having an opening, a vacuum chamber in the housing and in fluidic communication with the recess, and one or more piercing elements that are extendable through the opening to penetrate skin of the subject. The vacuum chamber can be configured for having a vacuum that draws the skin into the recess. The recess can be configured having a size or shape that enables an increased volume of the fluid sample to be accumulated in the skin drawn into the recess.